2009
DOI: 10.1097/icl.0b013e3181b93bd1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Protein and Lipid on Neutralization Times of Hydrogen Peroxide Care Regimens

Abstract: Tablet-based one-step disinfection systems neutralize at a slower rate than disc-based peroxide systems, but this difference is only significant during the first 20 minutes after the onset of neutralization. Neither lens deposition nor lens material plays a role in the speed of neutralization of peroxide-based systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Hydrogen peroxide provides its antimicrobial activity by destabilising organic material through oxidation to damage cell membranes and components [167,184]. Lens cases usually include a catalyst, such as a platinum coated disc for neutralisation of the solution once it has been poured into the case, taking approximately six hours to fully neutralise, although the majority of anti-microbial activity and neutralisation occurs within the first 40 min [185].…”
Section: Oxidative Systemsmentioning
confidence: 99%
“…Hydrogen peroxide provides its antimicrobial activity by destabilising organic material through oxidation to damage cell membranes and components [167,184]. Lens cases usually include a catalyst, such as a platinum coated disc for neutralisation of the solution once it has been poured into the case, taking approximately six hours to fully neutralise, although the majority of anti-microbial activity and neutralisation occurs within the first 40 min [185].…”
Section: Oxidative Systemsmentioning
confidence: 99%
“…7 Neutralization typically requires at least 6 hr, which can be an inconvenience for patients and may explain why more patients reported using MPS systems. 19 Another factor contributing to the lower usage of H2O2 may be practitioner apprehension about recommending H2O2 to patients, presumably because of concerns about patient compliance with the neutralization requirement and/or long term storage of CLs in neutralized peroxide solution. 20,21 However, only about 1% of H2O2 patients in this study reported having possible peroxide exposure leading to ocular discomfort.…”
Section: Discussionmentioning
confidence: 99%